Species of braconid wasps described by Christian Godfried Nees ab Esenbeck in 1811, 1812, 1816, 1818, 1834. A revisionary checklist (Hymenoptera, Braconidae) - Papp, J. (Zootaxa, 2016)
In his five publications Nees (1811–1834) described 263 braconid species originating mainly from Germany and, less in number, from a further seven countries in Europe. The braconid species were assigned to 19 genera: twelve have been created by him and the rest (seven genera) by three other authors. The majority of the species (218) remained valid, the rest of the names (45) were placed in synonymy (by other authors). By his descriptions the species and genera are more or less recognizable, nevertheless their redescriptions are promoting their unambiguous recognition. In the first checklist provided, the genera and species are presented following Nees’s original denominations and the current valid generic and species names are listed (denoted by an equals (=) sign). In the second checklist, the current valid generic and species names are compared with the original generic and species names. In the third checklist, the braconid species of 16 other authors included in Nees five publications are listed. New author’s names for three species are provided: Doryctes leucogaster Ziegler, 1834 (Bacon), Microgaster nigricans Gyllenhal, 1834 and Microplitis sordipes (Ziegler, 1834) (Microgaster); the author of these three species was Nees. The Nees Collection (braconid and other material) was destroyed at the end of the Second World War.